2009
DOI: 10.1111/j.1365-3091.2009.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic formation of gypsum and dolomite in a cold-water coral mound in the Porcupine Seabight, off Ireland

Abstract: Authigenic gypsum was found in a gravity core, retrieved from the top of Mound Perseverance, a giant cold-water coral mound in the Porcupine Basin, off Ireland. The occurrence of gypsum in such an environment is intriguing, because gypsum, a classic evaporitic mineral, is undersaturated with respect to sea water. Sedimentological, petrographic and isotopic evidence point to diagenetic formation of the gypsum, tied to oxidation of sedimentary sulphide minerals (i.e. pyrite). This oxidation is attributed to a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…A recent review of computed tomography (CT) scans in the geosciences (Cnudde and Boone, 2013) demonstrates the growing application possibilities of X-ray technology as well as the limits of the technique. Improvements in CT scanning allowed exploration of complex sedimentary structures through 3-D reconstructions, leading to improvement compared to classic 2-D imaging (Pirlet et al, 2010;Bendle et al, 2015). The method is based on the relative density of each voxel (i.e., volumetric pixel) constituting the chosen sample.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of computed tomography (CT) scans in the geosciences (Cnudde and Boone, 2013) demonstrates the growing application possibilities of X-ray technology as well as the limits of the technique. Improvements in CT scanning allowed exploration of complex sedimentary structures through 3-D reconstructions, leading to improvement compared to classic 2-D imaging (Pirlet et al, 2010;Bendle et al, 2015). The method is based on the relative density of each voxel (i.e., volumetric pixel) constituting the chosen sample.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced flow conditions led to erosion intervals, during which early diagenetic processes could overprint geochemical signals. The dissolution of coral skeletons and the formation of gypsum, pyrite and dolomite in those basal intervals display a striking similarity with the processes described by Pirlet et al (2010) on top of Mound Perseverance, further west in Porcupine Seabight.…”
Section: Mound Initiation Growth and Demisementioning
confidence: 56%
“…In mounds, such transport is an important factor of early diagenesis. Pirlet et al (2010) demonstrated that a bottom current-induced convective flow of oxidizing fluids in the shallow subsurface of a mound led to the formation of authigenic gypsum and to an early lithification of sediments close to the sediment-water interface. Modeling of full-mound flushing by Depreiter (2009) can explain the observed removal of a significant carbonate fraction, mainly aragonite, from recent mounds.…”
Section: Mounds At the Cross-roads Of External And Internal Fluxes Ofmentioning
confidence: 99%
“…An interesting experiment would be to drill a sequence of mounds from exposed ones to recently buried ones, to track in particular the diagenetic expression of the switch from open diagenetic system (the "mound flushing" stage of exposed mounds) to encapsulation, both in a proven pathway of advecting fluids (Melilla mound province, Alboran Sea, Morocco, Comas et al, 2009) and in a setting, possibly not affected by migrating fluids (Magellan -Perseverance mound suite, Porcupine Seabight, Huvenne et al, 2007;Pirlet et al, 2010).…”
Section: Mounds At the Cross-roads Of External And Internal Fluxes Ofmentioning
confidence: 99%